Nasal Aesthetic Evaluation Following Pre-Surgical Naso-Alveolar Molding Application: A Single-Blinded Cohort Retrospective Study in Indonesia - Bangun, Kristaninta; Sukasah, Chaula Luthfia; Kamayana, Jenisa Amanda Sandiarini; Basuki, Adi; Halim, Jessica; Nahdiyat, Nur Eulis Pujiastuti; Harsanto, Agatha Novell; Pramudita, Arvin (Jurnal Plastik Rekonstruksi, 2021)
Introduction: As a major facial aesthetic unit, the nose is one of the significant features in cleft lip and palate repair. The use of a naso-alveolar molding (NAM) device was known to help narrow the cleft gap and improve nasal aesthetics. This study aims to evaluate post-operative nasal morphology in unilateral cleft lip and palate patients who had used presurgical NAM, particularly in an established craniofacial centre in one of developing countries. Methods: A cohort retrospective study was conducted at Cleft Craniofacial Centre, Cipto Mangunkusumo Hospital Indonesia, comparing the nasal symmetry in unilateral cleft lip patients with and without prior application of NAM (NAM and control group), twelve months following primary cheiloplasty. Differences between the cleft and normal side were assessed using standard basilar view photographs based on five points nasal measurements. Results: A total of twelve patients were enrolled, six with a history of NAM application and six without (control). Overall nasal measurements confirmed a lower mean of differences in the NAM group compared to the control, showing statistically significant results in nostril height, nasal dome height, and columellar height (p <0.05). Conclusion: This study provides an insight that cleft lip patients with a history of NAM application had superior nasal symmetry compared to patients without presurgical NAM application 1-year post-cheiloplasty. Presurgical NAM application is recommended for patients with unilateral cleft lip and palate.